2013
DOI: 10.3892/mmr.2013.1715
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone alleviates injury in rats with adenine-induced chronic kidney disease

Abstract: Abstract. Rosiglitazone (ROG) has been shown to exert beneficial effects on glycemic control and renal protection. Circulatory fibroblast growth factor-23 (FGF-23) is a novel independent risk factor for chronic kidney disease (CKD) progression. The current study focused on how ROG impacts on injury of the kidney, and whether FGF-23 is involved in the process. A total of 24 male Sprague Dawley rats, weighing 250-280 g, were divided into four groups (n=6 per group): i) Normal; ii) ROG controls, treated with ROG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These findings are consistent with others 49–62 and our previous work 23 . In addition, the adenine-induced CKD in rodent models have been reported to cause cardiovascular damages 58 , including increase in left ventricular fibrosis, ventricular stiffness, and wall thickness 56 , increased blood pressure 56,62 , oxidative stress and inflammation including elevation in the activities of SOD, leukocyte infiltration, increased expression of NF-κB 60 , heme oxygenase-1, TNF-α and NOD-like receptor protein-3 56,60 , elevated levels of parathyroid hormone 60,63 , phosphate 56,60 , and anaemia with decrease in erythrocyte count, hematocrit, haemoglobin and erythropoietin 59 , and decrease in food intake 60 , similar to human subjects. This makes the adenine model to be a valid and highly reproducible model, and thereby justifies the use of the model for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with others 49–62 and our previous work 23 . In addition, the adenine-induced CKD in rodent models have been reported to cause cardiovascular damages 58 , including increase in left ventricular fibrosis, ventricular stiffness, and wall thickness 56 , increased blood pressure 56,62 , oxidative stress and inflammation including elevation in the activities of SOD, leukocyte infiltration, increased expression of NF-κB 60 , heme oxygenase-1, TNF-α and NOD-like receptor protein-3 56,60 , elevated levels of parathyroid hormone 60,63 , phosphate 56,60 , and anaemia with decrease in erythrocyte count, hematocrit, haemoglobin and erythropoietin 59 , and decrease in food intake 60 , similar to human subjects. This makes the adenine model to be a valid and highly reproducible model, and thereby justifies the use of the model for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of effective antidiabetic drug, PPARγ agonists not only conquer diabetic nephropathy, but they are also considered potential therapeutic agents in non-diabetic CKD ( Fogo, 2011 ). Previous studies have demonstrated that rosiglitazone could protect kidney from damage induced by several factors ( Huang et al, 2013 ; Kumar et al, 2013 ; Korolczuk et al, 2014 ). Pioglitazone attenuated renal ischemia-reperfusion injury through its anti-inflammatory and antioxidant effects ( Reel et al, 2013 ; Zou et al, 2013 ), reduced kidney damage in diabetic rats through increasing glomerular podocalyxin protein expression ( Peng et al, 2014 ) and provided renoprotection by interfering with the renin-angiotensin system and profibrotic proteins ( Ochodnicky et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eighty adult male Sprague Dawley rats 220 ± 20 gm and 6–8 weeks old were obtained from the animal house faculty of veterinary medicine, Zagazig University and were maintained under standard conditions for experimentation on rodents. Nephropathy was induced in rats via the administration of adenine (Sigma–Aldrich Chemical Co., St. Louis, MO, USA) 200 mg/kg body weight (b.wt) in 0.5% carboxymethyl cellulose (CMC) (Sigma–Aldrich Chemical Co., St. Louis, MO, USA) daily for 24 consecutive days [ 32 ].…”
Section: Methodsmentioning
confidence: 99%